2018
DOI: 10.4081/or.2017.7493
|View full text |Cite
|
Sign up to set email alerts
|

Complications after operative treatment of femoral shaft fractures in childhood and adolescence

Abstract: Purpose of the study was to retrospectively analyze the complication rates after operatively treated femoral shaft fractures in childhood and adolescence. Retrospective evaluation of 42 children with operatively treated femoral shaft fractures between 2000 and 2014. Fractures were classified as 27 A type, 12 B type and 3 C type fractures according the OTA/AO classification. 8 (19.05%) fractures were open. Age averaged 10.2 years (3-16). Fracture treatment was recorded as temporary or definitive external fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Reasons for these differences could be related to population differences and differences in regional surgical practice and trends. Overall the high rate of reoperation (15.9%) found among adolescents surgically treated for midshaft clavicle fractures is similar to the reoperation rate reported by Kruppa et al [ 18 ] among children and adolescents surgically treated for femoral shaft fractures (14.3%).…”
Section: Discussionsupporting
confidence: 87%
“…Reasons for these differences could be related to population differences and differences in regional surgical practice and trends. Overall the high rate of reoperation (15.9%) found among adolescents surgically treated for midshaft clavicle fractures is similar to the reoperation rate reported by Kruppa et al [ 18 ] among children and adolescents surgically treated for femoral shaft fractures (14.3%).…”
Section: Discussionsupporting
confidence: 87%
“…The interlocking intramedullary nails themselves have stress shielding, which can cause complications such as delayed bone healing or nonunion. Some studies have shown that [17], in adolescents with an average weight of 72 kilograms (53 to 99) and an average age of 15 years (14 to 16) who use interlocking intramedullary nails for femoral shaft fractures, one-third of patients have complications such as wound infection and bone nonunion. The study of Martus et al [8] shown some patients use locked intramedullary nail to treat long-term pain after femoral shaft fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Although union rate was reported up to 100% with a shorter hospital stay; however, it carries the risk of increased blood loss and the need for other surgery for plate removal [7] , [8] , [9] . In a study by Kruppa et al reporting on a cohort of children and adolescents treated for femoral shaft fractures using various methods, the authors reported an overall incidence of complications of 16.7%, 4.8% deep infection and 2.4% non-union, nearly all the complicated cases needed re-operation, hardware removal was performed in about 91% of the patients [10] .…”
Section: Discussionmentioning
confidence: 99%